Anthropogenic Aerosols Effects on Ice Clouds: A Review - Yang Yang; Run Liu (Atmosphere, 2022)
Since the ability of anthropogenic aerosols to act as ice nucleation particles has been recognized, the effect of anthropogenic aerosols on ice clouds has attracted increasing attentions. In recent years, some progress has been made in investigating the effects of anthropogenic aerosols on ice clouds. In this paper, we briefly review the study on the impact of anthropogenic aerosols on ice nuclei, properties and radiative forcing of ice clouds. Anthropogenic aerosols can form ice nuclei through homogeneous nucleation and heterogeneous nucleation. Convective strength can modulate the response of ice clouds to anthropogenic aerosols by affecting the nucleation activities. There have been large uncertainties in calculating the radiative forcing of anthropogenic aerosols on ice clouds in climate models. Further studies on the impact of anthropogenic aerosols on ice clouds are imperative to provide better parameterization schemes and reduce the uncertainties of aerosol indirect effects.